Project Based Learning Menghadapi Learning Loss Muatan IPS di SD IT Bina Insani Panggang Tahun Pelajaran 2021-2022 - Sri Yatun; Gunawan Sridiyatmiko (UM Purwokerto Press, 2022)
The Covid-19 pandemic has had a tremendous impact on the education sector. Changes in curriculum policies and teacher work systems lead to changes in the process of teaching and learning activities. Before the pandemic, teaching and learning activities took place face-to-face/offline at schools, while during the pandemic teaching and learning activities took place online/online and face-to-face meetings were limited. Changes in the learning system have a very significant impact. Students who are accustomed to participating in face-to-face learning activities will require a process of adapting, especially students who do not yet have infrastructure that supports the online learning process, such as cellphones, quotas and signals. The obstacles faced during the pandemic can result in learning loss or learning loss for students. SD IT Bina Insani Panggang is trying to deal with learning loss in learning social studies content with Project Based Learning. This research is a qualitative research. Research place at SD IT Bina Insani Panggang Gunungkidul. The research subjects were students of class I-VI SD IT Bina Insani Panggang. The results of the research are in the form of information about the implementation of Project Based Learning facing Learning Loss in learning social studies content at SD IT Bina Insani Panggang for the academic year 2021-2022.